(untitled) (Research, Society and Development, 2025)
Nephrotic syndrome is a disease associated with thromboembolic events, including pulmonary thromboembolism. According to guidelines such as KDIGO, these patients benefit from the use of anticoagulants for prevention and treatment, with warfarin being the most recommended. The use of novel oral anticoagulants (DOACs) has been increasingly expanding in clinical practice; however, their administration remains controversial in the literature for the prevention and treatment of thromboembolic events in individuals diagnosed with glomerulopathies. The objective of this article is to present a case report of a patient who was hospitalized in a tertiary hospital due to a pulmonary thromboembolism and was discharged on rivaroxaban therapy. The patient was readmitted one month after discharge due to worsening dyspnea associated with ventilator-dependent pain. A new angiotomography showed the presence of new areas of pulmonary infarction, despite being on therapeutic anticoagulation with rivaroxaban. On physical examination, symmetrical and painless edema of the lower limbs up to the knees was noted. During the investigation of the triggering factor, a 24-hour proteinuria test was requested, revealing 12g/24 hours, and anti-PLA2R positivity, confirming the diagnosis of primary membranous glomerulopathy.